APLIKASI EDIBLE FILM BERBASIS UBI JALAR KUNING YANG MENGANDUNG ANTIOKSIDAN UNTUK MEMPERPANJANG UMUR SIMPAN DODOL - , MONARISKA SITUMORANG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dodol is a traditional food from Java, especially Jogjakarta. Many people like dodol as a favorite food. Dodol was packed with plastic. But the use of synthetic materials impacted on environmental pollution because plastic canât be destroyed naturally. To reduce of plastics as food packaging is the use biodegradable packaging or edible packaging, one of them is edible film. Edible film from sweet potato starch with added sorbitol as plasticizer. Beside that also added the BHT with variation 100 ppm and 200 ppm to see the addition effect of BHT with the quality of dodol during storage. The data obtained were analyzed with the metjod of distinction statistical program, SPSS 16. The result showed the addition of BHT on edible film can change the characteristics of edible film such as tensile strength and water vapor permeability. Addition of BHT can decrease tensile strength of edible film and increase water vapor permeability of edible film. Dodol packed with edible film with addition of BHT is able to delay the detriment of dodol seen of quality parameters peroxide value and TBA value.